Exposure to the Chinese Famine in Early Life and the Risk of Metabolic Syndrome in Adulthood - Li, Yanping (American Diabetes Association, 2011)
OBJECTIVE: To examine whether exposure to the Chinese famine during fetal life and early childhood is associated with the risks of metabolic syndrome and whether this association is modified by later life environment. RESEARCH DESIGN AND METHODS: We used data of 7,874 adults born between 1954 and 1964 from the 2002 China National Nutrition and Health Survey. Famine exposure groups were defined as nonexposed; fetal exposed; and early childhood, midchildhood, or late childhood exposed. Excess death rate was used to determine the severity of the famine. The ATP III criteria were used for the definition of metabolic syndrome (three or more of the following variables: elevated fasting triglyceride levels, lower HDL cholesterol levels, elevated fasting glucose levels, higher waist circumference, high blood pressure). RESULTS: In severely affected famine areas, adults who were exposed to the famine during fetal life had a higher risk of metabolic syndrome, as compared with nonexposed subjects (odds ratio 3.13 [95% CI 1.24–7.89, P = 0.016]). Similar associations were observed among adults who were exposed to the famine during early childhood, but not for adults exposed to the famine during mid- or late childhood. Participants who were born in severely affected famine areas and had Western dietary habits in adulthood or were overweight in adulthood had a particularly high risk of metabolic syndrome in later life. CONCLUSIONS: Exposure to the Chinese famine during fetal life or infancy is associated with an increased risk of metabolic syndrome in adulthood. These associations are stronger among subjects with a Western dietary pattern or who were overweight in adulthood.